Renoprotective potentials of small molecule natural products targeting mitochondrial dysfunction - Rahman, Md. Ataur; Akter, Sumaya; Dorotea, Debra; Mazumder, Arpita; Uddin, Md. Naim; Hannan, Md. Abdul; Hossen, Muhammad Jahangir; Ahmed, Md. Selim; Kim, Woojin; Kim, Bonglee; Uddin, Md Jamal (Frontiers in Pharmacology, 2022)
Kidney diseases, including acute kidney injury (AKI) and chronic kidney disease (CKD), have become predominant clinical issues, socioeconomic load, and public health concerns worldwide. The kidney requires a high amount of energy, and mitochondria act as central organelle for the proper functioning of the kidney. Mitochondrial dysfunction has been well associated with the pathogenesis of AKI and CKD. Despite the challenges in drug discoveries, natural products and their structural analogs have been sought as an alternative therapeutic strategy. Many studies have demonstrated that small molecule natural products can improve renal function and ameliorate the progression of kidney diseases. This review summarized the nephroprotective effects of small molecule natural products, such as berberine, betulinic acid, celastrol, curcumin, salidroside, polydatin, and resveratrol. Treatment with small molecule natural products was shown to attenuate renal oxidative stress and mitochondrial DNA (mtDNA) damage, as well as restore mitochondrial biogenesis and mitochondrial dynamics in the kidneys against various injury stimuli. Thus, the small molecule natural products could be acknowledged as multi-target therapeutics and promising drugs to prevent kidney diseases, partially by attenuating mitochondrial dysfunction.